Preoperative and Postoperative Bone Mineral Density Change and Risk Factor Analysis in Patients with a GH-Secreting Pituitary Adenoma - Li’nan Qin; Xiaopeng Guo; Lu Gao; Zihao Wang; Chenzhe Feng; Kan Deng; Wei Lian; Bing Xing (International Journal of Endocrinology)
Purpose. This study analysed changes in bone mineral density (BMD) at different sites in patients with acromegaly and postoperative BMD changes and explored risk factors associated with BMD. Methods. Clinical data of 39 patients with growth hormone- (GH-) secreting pituitary adenomas and 29 patients with nonfunctioning pituitary adenomas who were newly diagnosed in neurosurgery from January 2016 to December 2018 were retrospectively analysed, including measurements of preoperative and postoperative BMD, serum GH glucose inhibition, random GH and IGF-1, and other anterior pituitary hormones. Results. The average patient age and disease duration were 43.74 (33.41–54.07) years and 72.15 (22.82–121.48) months, respectively. Compared with patients with nonfunctioning adenomas, patients with GH-secreting pituitary adenomas had significantly higher BMDs at L1, L2, femoral neck, Ward triangle, trochanter, femoral shaft, and total hip sites (p<0.05). The BMD Z score at L1 and femoral neck sites significantly increased (p<0.05). Thirteen patients underwent re-examination of BMD 1 year postsurgery, and the BMD Z score was reduced to normal levels at L1, L2, L3, L4, L1-L4, and L2-L4 compared with preoperative levels (p<0.05). Postoperative BMD Z scores in the femoral neck and total hip were significantly increased (p<0.05). Disease duration was negatively correlated with the lumbar-spine BMD Z score. IGF-1 burden was negatively correlated with the BMD Z score at L1 and L1–L4. Multiple regression analysis showed that IGF-1 burden was a risk factor for a BMD Z score decrease at L1 and L1–L4. Conclusion. BMD in patients with GH-secreting pituitary adenomas (compared with nonfunctional adenomas) increased at L1, L2, femoral neck, Ward triangle, trochanter, femoral shaft, and total hip sites. Lumbar-spine BMD Z score recovered to normal levels postsurgically when GH and IGF-1 levels were controlled. BMD Z score was negatively correlated with disease duration and IGF-1 burden in patients with GH-secreting pituitary adenomas, and IGF-1 burden was an independent risk factor for reduced lumbar-spine BMD Z score.